The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/w13243647
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Potential Soil Erosion and Sediment Yield: A Case Study of the Transboundary Chenab River Catchment

Abstract: Near real-time estimation of soil loss from river catchments is crucial for minimizing environmental degradation of complex river basins. The Chenab river is one of the most complex river basins of the world and is facing severe soil loss due to extreme hydrometeorological conditions, unpredictable hydrologic response, and complex orography. Resultantly, huge soil erosion and sediment yield (SY) not only cause irreversible environmental degradation in the Chenab river catchment but also deteriorate the downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 128 publications
0
12
0
Order By: Relevance
“…Te upper reaches are plateaus with mountains, while the middle region has steep and moderate gorges and the lower basin is fat. Te western parts of the watershed have basalt with shallow aquifers and are extremely vulnerable to the erosive activities of the surrounding rivers [18]. In general, the slope of each catchment varies from gentle to steeper at the outlet and in the middle of the watershed respectively.…”
Section: Topography Of the Areamentioning
confidence: 99%
“…Te upper reaches are plateaus with mountains, while the middle region has steep and moderate gorges and the lower basin is fat. Te western parts of the watershed have basalt with shallow aquifers and are extremely vulnerable to the erosive activities of the surrounding rivers [18]. In general, the slope of each catchment varies from gentle to steeper at the outlet and in the middle of the watershed respectively.…”
Section: Topography Of the Areamentioning
confidence: 99%
“…e northern parts of the watershed are covered by basaltic flows and are deeply dissected by the erosive activities of the surrounding rivers [24]. In general, the area's slope is characterized by varying from gentle at the outlet and northern parts to steeper through the middle of the watershed, so that high sediment accumulation possibilities are created over both the upper and lower portions of the watershed.…”
Section: Topographymentioning
confidence: 99%
“…The erosion and siltation processes have impacted the entire Blue Nile River Basin (Megersa et al, 2017 ; Mhazo et al, 2016 ). In addition to irreparable environmental impacts in the watershed, the erosion and deposition affect downstream water quality (Ali et al, 2021 ). It is reported that sedimentation and siltation affects all reservoirs, and while the problem cannot be completely eradicated, it may be managed by various methods on the upstream reservoir catchment (Leta & Chakravarti, 2017 ).…”
Section: Introductionmentioning
confidence: 99%